Diffusion-weighted MRI determined cerebral embolic infarction following transcatheter aortic valve implantation: assessment of predictive risk factors and the relationship to subsequent health status. Issue 1 (7th July 2011) - Fairbairn, Timothy A; Mather, Adam N; Bijsterveld, Petra; Worthy, Gillian; Currie, Stuart; Goddard, Anthony J P; Blackman, Daniel J; Plein, Sven; Greenwood, John P
Abstract : Background: 'Silent' cerebral infarction and stroke are complications of transcatheter aortic valve implantation (TAVI). Objective: To assess the occurrence of cerebral infarction, identify predictive risk factors and examine the impact on patient health-related quality of life (HRQoL). Methods: Cerebral diffusion weighted MRI of 31 patients with aortic stenosis undergoing CoreValve TAVI was carried out. HRQoL was assessed at baseline and at 30 days by SF-12v2 and EQ5D questionnaires. Results: New cerebral infarcts occurred in 24/31 patients (77%) and stroke in 2 (6%). Stroke was associated with a greater number and volume of cerebral infarcts. Age (r=0.37, p=0.042), severity of atheroma (arch and descending aorta; r=0.91, p<0.001, r=0.69, p=0.001, respectively) and catheterisation time (r=0.45, p=0.02) were predictors of the number of new cerebral infarcts. HRQoL improved overall: SF-12v2 physical component summary increased significantly (32.4±6.2 vs 36.5±7.2; p=0.03) with no significant change in mental component summary (43.5±11.7 vs 43.1±14.3; p=0.85). The EQ5D score and Visual Analogue Scale showed no significant change (0.56±0.26 vs 0.59±0.31; p=0.70, and 54.2±19 vs 58.2±24; p=0.43). Conclusion: Multiple small cerebral infarcts occurred in 77% of patients with TAVI. The majority of infarcts were 'silent' with clinical stroke being associated with a both higher infarct number and volume. Increased age and the severity of aortic arch atheroma were independent risk factors for the development of new cerebral infarcts. Overall HRQoL improved and there was no association between the number of new cerebral infarcts and altered health status.